First-feeding of hake (Merluccius hubbsi) larvae and prey availability in the North Patagonian spawning area - Viñas, Maria Delia (2000)
The diet of Merluccius hubbsi first-feeding larvae was analysed and related to food availability in stratified waters of the Patagonian spawning area. The gut contents of small larvae ranging from 2 to 4 mm SL, collected from five consecutive depth strata (upper 50 m of the water column), were examined. After dissection of the larvae, the prey items were stained with tolouidine blue. The feeding incidence, and the types, sizes and numbers of food particles per larvae were determined. The mean feeding incidence was 64.5 %. Food particles 45 to 136 μm in width constituted the bulk of the prey ingested, which consisted of nauplii and early copepodites of the small copepod species frequently found in the sampling area. The most abundant taxa among the gut contents were Paracalanus parvus. Oithona spp.. Acartia tonsa and members of Pseudocalanidae. The mean number of nauplii per larva was 4.4 times higher than the number of copepodites, but the volumetric ratio between the two groups was 1.4:1. The results of larval gut analysis were related to zooplankton distribution in the field. First-feeding strategies of hake and anchovy larvae growing in the area were compared.